Young hands, old books: Drawings by children in a fourteenth-century manuscript, LJS MS. 361 - Deborah Ellen Thorpe (Cogent Arts & Humanities, 2016)
This article scrutinises three marginal drawings in LJS 361, Kislak Center for Special Collections, Rare Books and Manuscripts, University of Pennsylvania Libraries. It first considers the provenance of the manuscript, questioning how it got into the hands of children. Then, it combines developmental psychology with close examination of the material evidence to develop a list of criteria to attribute the drawings to children. There is consideration of the features that help us estimate the age of the artists, and which indicate that one drawing was a collaborative effort between two children. A potential relationship is identified between the doodles and the subject matter of the text, prompting questions about pre-modern child education and literacy. Finally, the article considers the implications of this finding in both codicology and social history since these marginal illustrations demonstrate that children were active in the material life of medieval books.